Pengaruh Lokasi, Kualitas Pelayanan, Dan Harga Terhadap Kepuasan Konsumen Pasar Tradisional Di Kelurahan Pekan 2 Sigambal - Surya Gunawan Ritonga; Yuniman Zebua; Nova Jayanti Harahap (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
Traditional markets have been around for a long time and have been passed down from generation to generation until now, even though nowadays they are modern and technological, the role of traditional markets still plays an important role in people's lives. The existence of traditional markets makes it easier for people to meet their needs, starting from food needs, kitchen goods , so clothes are also available there at varying prices. Location, service quality and price greatly influence consumer satisfaction. This has been analyzed and proven by research carried out in order to find out this. The use of the t test aims to partially analyze the influence between the independent variables on the dependent variable. From the results of Table 6 above, it shows that The Location variable has a tcount value of 1.897 > a ttable value of 1.663 with a Sigcount value of 0.061 > a Sigtable value of 0.050. This means that the Location variable has a positive and insignificant effect on Consumer Satisfaction. From the results of Table 6 above, it shows that the Service Quality variable has a tcount value of 2.236 > ttable value of 1.663 with a Sigcount value of 0.028 < Sigtable value of 0.050. This means that the Service Quality variable has a positive and significant effect on Consumer Satisfaction. From the results of Table 6 above, it shows that the Price variable has a tcount value of 2.034 > ttable value of 1.663 with a Sigcount value of 0.045 < Sigtable value of 0.050. This means that the Price variable has a positive and significant effect on Consumer Satisfaction. The use of the F Test aims to analyze the influence simultaneously or together of the Location, Service Quality and Price variables on Consumer Satisfaction. The table below is a table of the F Test results: Based on the results of Table 7 above, it can be seen that the Fcount value is 44.364 > the Ftable value is 2.490 and the Fcount significance value is 0.000 < the Ftable value is 0.05.